The profile of cognitive style, logical thinking ability, and conceptual knowledge of electricity and magnetism topic based on prospective physics teachers' grade level. Issue 3 (February 2019) - Rahmawati, R; Rustaman, N Y; Hamidah, I; Rusdiana, D
Abstract: One of the efforts that can be done in designing classroom assessment is to mapping a number of variables that affect the physics learning process, especially on electricity and magnetism. In this research, mapping of cognitive style, logical thinking ability, and conceptual knowledge of electrical and magnetism topics aimed to know the pattern of change of three variables owned by prospective physics teachers based on grade level. This study is descriptive research with 95 respondents taken from one class for each level by random sampling. The results showed that cognitive style, logical thinking ability, and conceptual knowledge variables changed with linear pattern. This finding becomes one of the next considerations to design electricity and magnetism learning assessment in universities.